2022
DOI: 10.1364/optica.459812
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a triangular-lattice pattern in nonlinear wave mixing with optical vortices

Abstract: Preparation, control, and measurement of optical vortices are increasingly important, as they play essential roles in both fundamental science and optical technology applications. Spatial light modulation is the main approach behind the control strategies, although there are limitations concerning the controllable wavelength. It is therefore crucial to develop approaches that expand the spectral range of light modulation. Here, we demonstrate the modulation of light by light in nonlinear optical interactions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…11 This close connection between DFG and SPDC has initiated a number of new methods that are more efficient to characterize and harness the spatial correlation of photon pairs. 12,13 Taking advantage of the high photon flux in the seeded process, we show that a practical image coding scheme using the spatial correlation of photon pairs can be realized through DFG.…”
Section: Introductionmentioning
confidence: 98%
“…11 This close connection between DFG and SPDC has initiated a number of new methods that are more efficient to characterize and harness the spatial correlation of photon pairs. 12,13 Taking advantage of the high photon flux in the seeded process, we show that a practical image coding scheme using the spatial correlation of photon pairs can be realized through DFG.…”
Section: Introductionmentioning
confidence: 98%
“…9,10 Beyond linear optics, structured light control with nonlinear optics has become topical of late, 11 shifting the focus of attention from wavelength change and efficiency to spatial modal creation, control, and detection. This has led to a reinvention of the field with a modern twist, ushering in new selection rules [12][13][14] and processes [15][16][17][18] while fostering widereaching applications, including spatial mode creation [19][20][21] and detection, 22,23 image processing [24][25][26][27] and filtering, 28 holography, [29][30][31] enhanced interferometry, 32 high-dimensional teleportation, 33,34 as well as the development of modern nonlinear materials. [35][36][37][38] Unfortunately, the spatial structure of light becomes distorted in complex channels, [39][40][41][42] arresting its full potential.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have also witnessed a growing interest in the nonlinear frequency conversion of structured light 5 , 18 . In spatial domain, it was demonstrated that using OAM light as fundamental frequency light source, one can realize the image processing and mode detection during the process of upconversion imaging 19 , 20 , and by shaping the spatial shape of the pump source, one can enhance the performance of high-dimensional OAM frequency interface 21 24 . In time-frequency domain, by using the dispersion-engineered sum-frequency generation, the quantum pulse gate for harnessing and selecting the time-frequency mode has been realized 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%